A psychoanalytic analysis of Arthur "Boo" Radley in To Kill a Mockingbird - Naufal, Muhammad Farras; Nurhayati, Sulasih (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2025)
This study explores the character of Arthur “Boo” Radley in To Kill a Mockingbird through Sigmund Freud psychoanalytic lens, focusing on his repression, isolation, and unconscious motivations. Arthur, a reclusive figure misunderstood by society, serves as a vital symbol of innocence and resilience in the face of trauma. The novel's themes of alienation and moral growth are intricately connected to Arthur’s interactions with the Finch children and the broader community. A qualitative research design was conducted, using textual analysis to examine Arthur “Boo” Radley’s psychological development and the dynamics of his id, ego, and superego. Key passages involving Arthur were analyzed to uncover how his experiences of trauma and societal judgment influence his actions and internal conflicts. The study reveals that Arthur's repressive upbringing and community ostracism shaped his unconscious desire for connection, which manifests in his small yet significant acts of kindness toward Scout and Jem. Findings suggest that Arthur “Boo” Radley’s character provides a profound commentary on the impact of trauma, the resilience of human kindness, and the importance of empathy in overcoming societal prejudices. His role as a moral catalyst for the Finch children highlights the novel's broader themes of justice, compassion, and the need to challenge preconceived notions. By analyzing Arthur “Boo” Radley, this study contributes to understanding the psychological underpinnings of literary characters and their relevance to societal issues.